A field guide to the permanent sample plots in the reduced-impact logging block 27 at CIFOR Malinau research forest East Kalimantan - Kartawinata, K.; Priyadi, H.; Sheil, Douglas; Riswan, S.; Sist, P.; Machfudh (Center for International Forestry Research, 2006)
A set of Permanent Sample Plots (PSP) was established in the lowland mixed dipetrocarp forest within PT Inhutani II concession at Malinau (2º45’ – 3º15’N, 116º30’), East Kalimantan (Figure 1). They were designed for comparative studies of conventional logging (CNV) and reduced-impact logging (RIL) techniques under the ITTO Project PD 12/97 Rev.1 (F), Forest, Science and Sustainability: Bulungan Model Forest. The Malinau concession is located about 30 km to the East of CIFOR’s Bulungan Research Forest in a forest area with elevation between 100 m to 300 m above sea level. The terrain is undulating with slopes ranging from 10% to 70%. The mean annual rainfall in the area is 3.790 mm, with the number of wet months of more than 9 months per year. This pocket guideline is intended to give visitors to PSPs information on how to access to the location of plots and distribution of trees with dbh = 20cm in each plot. The CIFOR’s Seturan station is used as a starting point to travel to the plots.